1994
DOI: 10.2466/pr0.1994.74.1.227
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Indonesian and American College Students' Attitudes toward Homosexuality

Abstract: Indonesian and U.S. college students were compared to assess whether an interaction of sex of subject by sex of target on attitudes toward homosexuals would be replicated cross-culturally. The Indonesian sample was expected to hold more traditional attitudes toward women's gender-role behavior which was expected to override the interaction of sex of subject by sex of target. Knowledge of AIDS was expected to be correlated with attitudes toward homosexuals. Analysis showed that the interaction of sex of subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…I also wrote to five researchers who used the AWS within the past 5 years but did not report means in their articles. Of these, three (Brems & Wagner, 1994; Chia, Moore, & Lam, 1994;Kyes, 1994) replied, for a response rate of 60%. In addition, I included a recent sample of the 15-item AWS, which I collected at the University of Michigan in 1995 (n = 71 males; 98 females).…”
mentioning
confidence: 99%
“…I also wrote to five researchers who used the AWS within the past 5 years but did not report means in their articles. Of these, three (Brems & Wagner, 1994; Chia, Moore, & Lam, 1994;Kyes, 1994) replied, for a response rate of 60%. In addition, I included a recent sample of the 15-item AWS, which I collected at the University of Michigan in 1995 (n = 71 males; 98 females).…”
mentioning
confidence: 99%
“…Women, on the other hand, appear much less likely to show antigay bias. Some researchers have argued that women do show antigay bias, but that their bias is against lesbians exclusively (Kyes & Tumbelaka, 1993); however, the bulk of research in this area has found antigay bias to be, for the most part, a male phenomenon (Hansen, 1982;Herek & Capitanio, 1999;Johnson, Brems, & Alford-Keating, 1997;Kite & Whitley, 1998;Kunkel & Temple, 1992;Larsen, Reed, & Hoffman, 1980;Yang, 1998). Johnson et al (1997) reported that women, compared to men, had a less negative response to gays and lesbians with regard to their own level of discomfort while being close to them, and that women tended to be more responsive to the civil rights of gays.…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies have found that heterosexuals with positive attitudes towards homosexuality are more likely to be female, young, non-religious, well-educated, politically liberal or moderate, and those with close personal contact with homosexual men and women (Haddock et al Political and Sexual Attitudes 311 1993; Herek 1994Herek , 1988Kite and Deaux 1986;Kite 1984;Larsen et al 1980;Morin and Garfinkle 1978;Thompson et al 1985). They are also more likely to have positive attitudes towards other minority groups (Herek 1991) and are less likely to support traditional gender roles (Kyes and Tumbelaka 1994). Hendrick and Hendrick (1987) explored the relationship between religious beliefs and sexual attitudes with two samples of students using their Sexual Attitude Scale.…”
Section: Main Hypothesesmentioning
confidence: 94%
“…Brazilians are more liberal with respect to religion, as well as less gender stratified in terms of sexuality as other studies have shown (Kyes and Tumbelaka 1994). Much has been said about how people classify homosexuality in different societies.…”
Section: Cultural Attitudes Toward Sexmentioning
confidence: 95%